Relative Age-Related Biases in Objective and Subjective Assessments of Performance in Talented Youth Soccer Players - Daniel Leyhr; Daniel Leyhr; Fynn Bergmann; Robert Schreiner; David Mann; Damir Dugandzic; Oliver Höner (Frontiers Media S.A., 2021)
Talent research has recommended that multidimensional assessments of performance are needed to improve the identification and development of talented young athletes. However, factors such as the relative age effect may cloud our ability to assess factors related to performance. The aim of this study was to determine the extent of any relationship between soccer players' chronological and relative age, and objective and subjective performance assessments. Data for highly talented male soccer players selected into the German Soccer Associations' talent promotion program (N = 16,138) for U12 to U15 age groups (Mage = 12.62 ± 1.04 years) were examined. Besides anthropometric assessments, players completed a battery of five motor tests that objectively assessed speed abilities and technical skills (specifically sprint, agility, dribbling, ball control, and juggling). In addition, coaches subjectively rated players on their kicking, tactical, and psychosocial skills, as well as providing holistic evaluations of each player's current and future performance levels. Correlation analyses were used to investigate the extent of any relationships between the chronological and relative age of players and their results for each of the assessments. A strong linear decrease in the frequency of later-born players confirmed the overrepresentation of early-born players in all age groups (0.92 ≤ |r| ≤ 0.95, each p < 0.001). From U12 to U15, significant (each p < 0.001) correlations were found between the chronological age of players and their height (|r| = 0.70), weight (|r| = 0.69), speed abilities (|r| = 0.38), and technical skills (|r| = 0.43). When evaluating each age group separately, small effects were found when correlating relative age with the anthropometric assessments (0.18 ≤ |r| ≤ 0.26), and only trivial effects with speed abilities and technical skills (0.01 ≤ |r| ≤ 0.06). Similarly, low correlations were found for the subjective evaluations of kicking, tactical, and psychosocial skills with chronological age across age groups (0.03 ≤ |r| ≤ 0.07), and with relative age in each age group (0.01 ≤ |r| ≤ 0.11). The results show a skewed distribution toward early-born players and-in reference to their relative age-advanced performance in late-born athletes. However, trends toward a better holistic rating of early-born players for current and future performance levels were found. Coaches should be aware of these effects during talent selection, but also when interpreting results from subjective and objective assessments of performance.